Efficacy and safety of conduction system pacing in heart failure patients with non-left bundle branch block morphology: a systematic review and meta-analysis - Thu, Kaung Myat; Antoun, Ibrahim; Eldesouky, Mahmoud; Abdelrazik, Ahmed; Thaint, May Myat; Ng, G. André; Ibrahim, Mokhtar (Frontiers in Physiology, 2025)
BackgroundConduction system pacing, including His bundle pacing and left bundle branch area pacing, has emerged as a physiological alternative to biventricular pacing (BiVP) for cardiac resynchronisation therapy (CRT). BiVP benefits patients with left bundle branch block (LBBB), but outcomes in non-LBBB morphologies are inconsistent. We synthesised the evidence for CSP in heart failure patients with non-LBBB conduction patterns.MethodsWe performed a systematic review and meta-analysis (PROSPERO CRD420251015905) of 21 studies (11 with quantitative data; n = 480). Comparative outcomes (CSP vs. BiVP) and baseline vs. follow-up CSP changes were pooled. Primary endpoints were left ventricular ejection fraction (LVEF), left ventricular end-diastolic diameter (LVEDD), New York Heart Association (NYHA) class, and QRS duration. Secondary endpoints included heart failure hospitalisation and all-cause mortality.ResultsIn head-to-head analyses (198 patients; 99 per arm), CSP conferred a mean + 5.83% LVEF benefit (95% CI 3.06–8.60; p < 0.0001; I2 = 0%), reduced LVEDD by 3.87 mm (95% CI 2.53–5.21; p < 0.001), improved NYHA class by −0.30 (95% CI –0.46 to −0.13; p = 0.0004), and narrowed QRS (SMD –0.91; 95% CI –1.18 to −0.64; p < 0.00001). CSP also halved HF hospitalisation risk (RR 0.44; 95% CI 0.24–0.81; p = 0.008; I2 = 0%). In single-arm baseline and follow-up analyses (480 patients), CSP yielded a mean + 8.91% LVEF, −2.95 mm LVEDD, SMD –1.37 NYHA, and SMD –1.21 QRS (p < 0.0001).ConclusionIn non-LBBB heart failure, CSP delivers substantial improvements in ventricular systolic function, reverse remodelling, symptoms, and electrical synchrony versus BiVP, with reduced HF hospitalisation. These findings position CSP as a promising BiVP strategy for a traditionally non-responder subgroup and warrant confirmation in large, randomised trials.